The New Frontier: Implementing OpenAthens at UNC Charlotte. Issue 1 (2nd January 2021) - Blankemeyer, Bethany; Siler, Liz; Tokoro, Shoko
Abstract: As vendors move away from IP authentication due to security concerns and a need for a more reliable method, libraries need to start considering other options for making their electronic resources available to users remotely. In 2018, the University of North Carolina, Charlotte (UNC Charlotte) made the decision to move from EZproxy to OpenAthens. This presentation will discuss the decision to make this change, the implementation process, and the ongoing maintenance and troubleshooting of OpenAthens.